2017
DOI: 10.1002/ccr3.1314
|View full text |Cite
|
Sign up to set email alerts
|

Graft‐versus‐host disease, a rare complication after orthotopic liver transplantation

Abstract: Key Clinical MessageAcute graft‐versus‐host disease (GVHD) after orthotopic liver transplantation (OLT) is a rare but fatal complication that poses a major diagnostic and therapeutic challenge. Our case highlights the need for further studies to develop therapeutic modalities to improve outcomes in patients who develop GHVD following OLT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
2
0
2
Order By: Relevance
“…Increasing immunosuppressive therapy is frequently used in the therapy for GvHD following LT. 2 , 3 , 11 13 , 15 , 16 , 18 , 19 , 21 , 22 , 24 , 25 , 28 30 , 33 , 35 , 37 , 40 45 , 48 , 49 , 51 55 , 57 , 58 , 60 , 61 , 64 , 65 , 68 , 69 , 71 , 74 , 75 , 77 , 78 , 80 – 83 , 86 88 , 90 , 94 , 95 , 98 103 , 106 108 , 111 , 112 , 114 , 116 119 , 122 127 , 130 , 132 , 134 , 142 Undoubtedly, increased immunosuppression frequently leads to toxicity and infection, resulting in septic shock. 19 The treatment of GvHD with corticosteroids 4 , 11 , 13 , 19 , 21 , 33 , 36 , 38 , 39 ,…”
Section: Discussionmentioning
confidence: 99%
“…Increasing immunosuppressive therapy is frequently used in the therapy for GvHD following LT. 2 , 3 , 11 13 , 15 , 16 , 18 , 19 , 21 , 22 , 24 , 25 , 28 30 , 33 , 35 , 37 , 40 45 , 48 , 49 , 51 55 , 57 , 58 , 60 , 61 , 64 , 65 , 68 , 69 , 71 , 74 , 75 , 77 , 78 , 80 – 83 , 86 88 , 90 , 94 , 95 , 98 103 , 106 108 , 111 , 112 , 114 , 116 119 , 122 127 , 130 , 132 , 134 , 142 Undoubtedly, increased immunosuppression frequently leads to toxicity and infection, resulting in septic shock. 19 The treatment of GvHD with corticosteroids 4 , 11 , 13 , 19 , 21 , 33 , 36 , 38 , 39 ,…”
Section: Discussionmentioning
confidence: 99%
“…Duplicates excluded were the reports by Kuball et al (Schuchmann et al reported their patient ), by Sudhindran et al and Taylor et al (Key et al had described their patients ), and by Neumann et al (Kohler et al had previously published their patient ). A total of 78 studies were withheld, in which a total of 150 patients with LTx‐associated GVHD were identified …”
Section: Methodsmentioning
confidence: 99%
“…-Поражение желудочно-кишечного тракта наиболее часто проявляется диареей (у 54% реципиентов) [4]. Может наблюдаться изъязвление слизистой рта [10], язвенное поражение пищевода [15]. В нашем первом наблюдении имел место выраженный гастрит, дуоденит; описаны также илеит и колит, которые могут привести к развитию кишечной непроходимости [11] или желудочнокишечному кровотечению [14].…”
Section: Abstract: Liver Transplantation Graft-versus-host Diseaseunclassified
“…Диагностика РТПХ основана на гистологическом исследовании пораженной ткани. Чаще всего диагноз ставится на основе материала из ЖКТ [20] или биопсии кожи [13,15]. Для дифференциального диагноза между различными дерматологическими заболеваниями могут быть использованы иммуногистохимические методы [21].…”
Section: Abstract: Liver Transplantation Graft-versus-host Diseaseunclassified